Recovering Greater Fungal Diversity from Pristine and Diesel Fuel Contaminated Sub-Antarctic Soil Through Cultivation Using Both a High and a Low Nutrient Media Approach - Ferrari, Belinda C.; Zhang, Chengdong; Van Dorst, Josie (Frontiers in Microbiology, 2011)
Novel cultivation strategies for bacteria are widespread and are well described for recovering greater diversity from the hitherto unculturable majority. While similar approaches have not been demonstrated for fungi it has been suggested that of the 1.5 million estimated species less than 5% have been recovered into pure culture. Fungi are known to be involved in many degradative processes, including the breakdown of hydrocarbons, and it has been speculated that in Polar Regions they contribute significantly to bioremediation of soils contaminated with hydrocarbons. Given the biotechnological potential of fungi there is a need to increase efforts for greater species recovery, particularly from extreme environments such as sub-Antarctic Macquarie Island. In this study, like the hitherto unculturable bacteria, high concentrations of nutrients selected for predominantly different species to that recovered using low nutrient media. By combining both approaches to cultivation from contaminated and non-contaminated soils, 99 fungal species were recovered, including 42 yet unidentified species, several of which were isolated from soils containing high concentrations of diesel fuel. These novel species will now be characterized for their potential role in hydrocarbon degradation.